An Analysis of Hedonic Behavior Portrayed in Shania Twain’s Selected Song Lyric: English - Imtihan Hanim; Rahmi Aulia Nurdini (Prodi Tadris Bahasa Inggris, 2023)
This research aims to describe the hedonism portrayed in Shania Twain’s song. Moreover, it also aims at describing the negative effect of hedonism on young people’s futures. The objective of this study is to analyze the hedonic behavior expressed in the song lyrics and also to describe the negative impact of hedonism, especially for the younger generation, as reflected in the song.